Psychological Factors Contributing to the Financial Well-Being of an Individual : A Review of Empirical Literature - Shobha, T. S.; Chakraborty, Suman (Indian Journal of Finance, 2017)
Financial well-being is a yardstick for the measurement of individuals’ financial security and their ability to make financial choices both in the present and future. Financial well-being in its perceptual nature is the most effective and reliable measure of the construct. Review of literature for financial well-being indicated that beyond the demographic, social, and economic factors, it is the psychological factors that have a greater impact on the financial well-being of an individual. These psychological factors needed further investigation for identification of specific psychological factors affecting financial well-being. This study attempted to analyze empirical and scholarly research findings. Twenty five papers downloaded from various electronic databases and from various peer reviewed journals in the area of financial well-being during 2000-2016 were considered for the present study. Review of selected papers suggested significant gaps pertaining to the interaction of psychology with financial well-being and also identified positive financial behaviours like financial literacy and propensity to plan affecting financial well-being. This assemblage of reviewed research papers will be useful for the academia and industry to cultivate understanding on the psychological rumblings of an individual and would promote positive financial behaviours leading to greater financial well-being.